Experimental modelling of clogging dynamics for rapid filtering of monodisperse and polydisperse suspensions - Lalitan, Hanzel Hartley (2017)
Rapid sand filters have been widely used in water purification system. The use of dual- and tri- media granular filters had gradually replaced rapid sand filters, owing to their greater ability in alleviating head loss development rate. However, the actual design and operations are primarily empirical due to a lack of apprehension on the clogging dynamism within the filter bed. The objective of this study was to better understand the clogging dynamics within a conventional pressurized dual-media filter column deploying sand and granular activated carbon (GAC). A tool for predicting the filter’s solids removal capability at different depths, under varied influent conditions was proposed. The constitutive mass transport equation was employed to quantify the removal of the influent particles (R_c) within the filter during effective filtration stage by assuming negligible diffusion and dominant bulk movement in y-direction. In addition, dimensionless analysis and Π-terms calibration were also utilized for developing the predictive tool. Generally, positive agreement with less than 10% deviations was achieved between the experimental and predicted results. We are hopeful that the predictive tool would assist operators in improving the design and operations of the filter to achieve the required removal efficiency.